A split axilla comparison study of axillary hair removal with low fluence high repetition rate 810 nm diode laser vs. high fluence low repetition rate 1064 nm Nd:YAG laser - R. Wanitphakdeedecha (2018)
Background A low fluence, high repetition rate 810 nm diode laser using constant motion technique has been recently introduced with advantages of less treatment discomfort and fewer side effects compared with traditional laser hair removal. Objective To compare hair reduction and side effects of low fluence high repetition rate 810 nm diode with high fluence low repetition rate 1064 nm Nd:YAG lasers. Methods Forty-nine subjects were randomly received five monthly treatments with diode laser on one side of their axilla and long-pulsed Nd:YAG laser on the other side. Hair count was recorded at baseline, 1- and 6-month follow-up visits. Results Percentage of axillary hair reduction at 1-month follow-up visit after receiving diode and Nd:YAG laser treatment were 71.0% and 82.3%, respectively, and at 6-month follow-up were 35.7% and 54.2%, respectively. There were significant differences in hair reduction between both laser systems at 1- and 6-month follow-ups (P < 0.001 and P < 0.001, respectively). Patients reported lower pain on the diode laser side (P < 0.001). Side effects of both laser systems were mild and transient erythema and swelling. Conclusions High fluence low repetition rate Nd:YAG laser was superior in hair reduction and provided higher patient satisfaction. However, low fluence high repetition rate diode laser was less painful. © 2011 European Academy of Dermatology and Venereology.